Desert of memory and memories: a reflection on the female subject from the Wayuu worldview in the narrative of Vicenta Siosi Pino and Estercilia Simanca Pushaina (2024)
This article examines the configuration of the female subject in the literary discourse of Wayuu writers Vicenta Siosi Pino and Estercilia Simanca Pushaina, exploring the connections between memories and events that shape the cultural memory of their community. From this point of view, an analysis is proposed on the relevance of the past when revealing traces of historical events that set a precedent within the oral tradition of the ethnic group. In this regard, the main finding is that, through the fictional content of their narrated testimonies, a link is established between culture, the contemporary world, and the worldview of women as a proposal for continuity or rupture with the implications of fulfilling this role within the community. This role emerges as a result of socio-historical evolution, serving as a metaphor for the past and for the social practices established by the Wayuu people.